ENSINO MÉDIO INTEGRADO: o estágio como um dos elementos articuladores da formação geral e profissional - Ribeiro, Silvia Fernanda Martins Dias (2011)
This study investigated the stage as one of the elements of the articulators high school integrated technical vocational training within the framework of the Federal Institute of Education Science and technology of Maranhão São Luís, IFMA Campus Monte Castelo. The school was integrated from the practice of the stage and their contribution to the training of students from the stage at IFMA electronics technician Course. It was considered the internship as an Education Act which allows the drive theory and practice. In this context, it aimed to understand how this can be an educational Act articulator element integrated training and at the same time contribute to the training and integration of students into the world of work. Cropping history held objective contextualize the educational policies in Brazil, with emphasis on the proposal for integration of high school with vocational education. In this respect, discussions focused on the globalisation of capital, productive restructuring and the influence of neo-liberal ideology, as well as its impacts on reforms of the State and professional education in Brazil. The theoretical-methodological route undertaken understood bibliographical analysis, documentary and empirical research with data collection and use of the questionnaire as a research tool. It was examined whether the object of study from the dialectical method and for their preparation was with the theoretical contribution of important authors like Marx and Engels, Gramsci, Mészaros, Manacorda, Antunes, Pistrak, Kuenzer, Ramos, Frigotto, Cash, Martins, Oliveira and Kings and other authors who contributed to the conduct of the study. Through this research concluded that the stage is an important axis articulator in integrated training, enabling students to objective conditions to understand the theory and practice. It was noted that, for its proper functioning, it is necessary for the monitoring of IFMA and technical supervisors to comply with the law of Stages and other regulations that govern it. It was found that the stage represents a step of technical-professional education, while have the possibility to prepare for the world of work. However, for this to occur, the challenges encountered have mentioned the need for more systematic monitoring of IFMA students in the fields of stage. Emphasized that the student sees vocational training in this step the possibility of continuation of their studies, albeit in different area in which it is inserted.